Analisis Flexing Photocard K-Pop di Media Sosial dalam Pembentukan Perilaku Panic Buying di Kalangan Penggemar - Sekarwangi, Dela; Arsyam, Andi Wulandari; Damto, Kinanthi Sekarningtiyas; Zaky, Muhammad (YASIN, 2025)
The phenomenon of flexing K-Pop photocards on social media has become increasingly prominent within digital fandom communities; however, studies on its impact on adolescents’ consumer behavior remain limited. This study aims to analyze the contribution of photocard flexing activities to the emergence of panic buying behavior among K-Pop fans, particularly through social mechanisms such as community pressure and the effect of Fear of Missing Out (FoMO). A descriptive qualitative approach was employed, with data collected through semi-structured interviews involving informants active on social media and experienced in panic buying, as well as documentation of posts from Instagram, TikTok, and X platforms. Data were analyzed using a thematic approach based on the Lifestyle Exposure Theory (LET) framework. The findings reveal that high exposure to flexing content, when combined with FoMO and social pressure within fan communities, significantly triggers excessive impulsive buying behavior. These findings reinforce the LET framework, which posits that digital lifestyles increase exposure to consumerist stimuli. The study concludes that social media plays a crucial role in shaping risky emotional consumption patterns, highlighting the importance of digital literacy as a preventive strategy. The implications of this research include the enrichment of literature on digital consumer behavior and practical recommendations for governments, educational institutions, and fandom communities to design educational interventions aimed at mitigating the psychological and social effects of panic buying. This study also opens avenues for further research on the role of social media algorithms in mediating adolescents’ consumption patterns.